Kajian Molekuler Layu Buah Muda Kakao (Theobroma cacao L.): Ekspresi TcPIN1 Like Gene - Yohana Theresia Astuti; Kumala Dewi; Santosa Santosa; A. Adi Prawoto (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
This experiment was carried out to evaluate the expression of TcPIN1 like gene in cocoa (Theobroma cacao L.). DNA and RNA were extracted from 7 weeks old of both healthy and cherelle wilt cocoa pods. PCR was done with two primer set based on PIN1 sequenced of Arabidopsis. Primer PIN1-1: Forward: taaggtgatgccaccaacaa; Reverse: gccatgaacaacccaagact. Primer PIN!-2: Forward: tttgtgtggagctcaagtgc; Reverse: ctgcgtcgttttgttgctta. RT-PCR was done with primer PIN1-2. The results showed that TcPIN1-2 like gene was found in healthy young pods, but not availabe in cherelle wilt pods of cocoa.